The Political Mediatization of the Golkar Party in West Sumatra - Arifuddin, Muhammad Thaufan; Darwis, Yuliandre; Dalmenda, M. A.; Rinaldi, Rinaldi; Yulia, Vitania (Jurnal Media dan Komunikasi Indonesia, 2025)
This study addresses a critical gap in the scholarship on the mediatization of political parties at the local level in post-Suharto Indonesia, namely the limited attention to how party–media interactions unfold outside the national arena and beyond Java-centric analyses. By examining the case of the Golkar Party in West Sumatra, this article shows how local dynamics shape distinctive patterns of political communication and mediatization. Drawing on in-depth interviews, intensive observation, and documentary analysis, including local newspaper coverage from Singgalang, the study demonstrates that Golkar has strategically employed mediatization to reinforce organizational networks, disseminate political and social programs, and mobilize electoral support. At the same time, the case reveals persistent constraints such as polarization, money politics, and dynastic influence, which highlight the limits of mediatization in advancing democratic consolidation at the local level. By situating the West Sumatra case against broader Indonesian patterns, this article makes a novel theoretical contribution to political mediatization by illustrating how local socio-political contexts condition party–media relations in ways that complicate assumptions derived from national-level studies.